2019
DOI: 10.1371/journal.pone.0220528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple stressors associated with agriculture on stream macroinvertebrate communities in a tropical catchment

Abstract: Tropical forests are declining at unprecedented rates in favour of agriculture, and streams can be severely impacted due to effects of multiple stressors that have rarely been considered together in tropical studies. We studied the effects of multiple stressors associated with agricultural practices (pesticide toxicity, nutrient enrichment and habitat alteration–quantified as TU max , soluble reactive phosphorus concentration and sedimentation, respectively) on macroinvertebrate communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 49 publications
6
14
0
1
Order By: Relevance
“…In addition, our rarefaction/extrapolation approach showed that this diversity is still under-sampled across sites both within the PCW and along the Isthmus of Panama (Fig 3). These findings confirm that the diversity of freshwater macroinvertebrates in Neotropical environments is largely under-studied [33,69,70], and could be much higher than previously thought. In particular, these findings highlight the fact that there is limited published research using genetic methods to study macroinvertebrate diversity in this region.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, our rarefaction/extrapolation approach showed that this diversity is still under-sampled across sites both within the PCW and along the Isthmus of Panama (Fig 3). These findings confirm that the diversity of freshwater macroinvertebrates in Neotropical environments is largely under-studied [33,69,70], and could be much higher than previously thought. In particular, these findings highlight the fact that there is limited published research using genetic methods to study macroinvertebrate diversity in this region.…”
Section: Discussionsupporting
confidence: 87%
“…Assessing the patterns and drivers of macroinvertebrate diversity at different scales is particularly relevant, given the increasing rate of environmental degradation in Neotropical regions [ 30 33 ]. This includes alterations such as introduction of alien species [ 34 , 35 ], the development of megaprojects [ 36 ], habitat degradation, water pollution, and climate change [ 30 , 33 , 37 , 38 ]⁠. As a consequence, a large portion of this biodiversity risks being lost before discovery.…”
Section: Introductionmentioning
confidence: 99%
“…These findings confirm that the diversity of freshwater macroinvertebrates in Neotropical environments is largely understudied [10,34,68], and could be much higher than previously thought. In addition, the fact that only a small number of specimens from these taxa matched available sequences in public databases further highlights the potential for biodiversity discovery in Neotropical freshwater environments.…”
Section: Discussionsupporting
confidence: 86%
“…Assessing the patterns and drivers of macroinvertebrate diversity at different scales is particularly relevant, given the increasing rate of environmental degradation in Neotropical regions [3134]. This includes alterations such as introduction of alien species [35,36], habitat degradation, water pollution, and climate change [31,34,37,38]□. In consequence, a large portion of this biodiversity risks being lost before discovery.…”
Section: Introductionmentioning
confidence: 99%
“…We addressed research gaps in a microcosm experiment, where we examined the effects of chlorothalonil (a common fungicide in agriculture and forestry worldwide; e.g., Du Gas et al, 2017;Cornejo et al, 2019) on microbial and invertebrate-mediated decomposition of litter of several riparian plant species, individually and mixed. We used a common detritivorous caddisfly and quantified its survival and growth, and we determined AH sporulation rate, taxon richness and assemblage composition, in response to (1) litter pre-treated with the fungicide, (2) waterborne fungicide, and (3) both exposure modes simultaneously.…”
Section: Introductionmentioning
confidence: 99%